Online Learning in Pandemic Era: Readiness and Obstacles English Teachers - Syarfuni Syarfuni; Maulizan ZA; Aan Iswandi (Almufi Journal of Measurement, Assessment, and Evaluation Education, 2021)
This study aimed to know the obstacles faced by the teachers while distance learning at Junior High school Banda Aceh. This research employed a descriptive qualitative method. The research participants were the three English teachers. The instrument of collecting the data used in this study was an interview. The objectives of this research were to know the teachers' readiness when distance learning and to know the obstacles faced by the teachers while distance learning. The result revealed that three Englishteachers' readiness is good because their preparation when distance learning is still well. The teachers actively shared the lesson on a group in Whatsaap, ensuring students understandind. The teachers are open to the students if they do not understand the teachers available to meet them one by one. The obstacles of three English teachers are coming up from the student because the students sometimes do not have a mobile phone to study or there is no quota, the students often forget their class, so they miss the lesson and the teachers are questions themselves whether the lesson is accepted well of the students or not. However, the teachers tried their best to ensure the teaching and learning process is run well.